Simulation and implementation of memristive chaotic system and its application for communication systems - Sahin, M. E.; Taskiran, Z. G. Cam; Guler, H.; Hamamci, S. E. (Elsevier Science Sa, 2019)
One of the most popular applications for chaotic systems is secure communication. The main purpose is to hide the information signal to be transmitted in a secure way, into a chaotic signal which is difficult to detect, and then to recover the information signal again. In response to this, memristor discovered by Leon O. Chua, known as the fourth basic element or the missing relationship can be implemented in chaotic circuit for a secure communication. The memristor based chaotic circuits which consist of three basic elements, have been used to obtain chaotic secure communication scheme in this paper. Using numerical simulation methods, including phase portraits, the largest Lyapunov exponents and bifurcation diagrams, the nonlinear dynamics are examined. In this respect, the advantage of chaotic feature of memristor and a memristor-based system was benefited for masking chaotic signals which are complicated to be analysed in communication systems. Therefore, the system was modelled with the help of LabVIEW and circuit with chaotic specialty was implemented in a secure communication. Simulation results confirm that the constituted design is likely to be utilizable in a secure communications application. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Memristor; Chaos; LabVIEW; Secure communication